Awareness to weight stigma: the effect of a multi-approach course unit on weight-related stigmatization among medical students - Ruck, Jessica; Krauthausen, Maike; Tiedemann, Elena; Koch, Martin J.; Simmenroth, Anne (Frontiers in Education, 2025)
BackgroundWeight bias and stigma are prevalent problems in health care professionals and medical students. They have consequences on care quality and, thus, on health of patients with overweight and obesity. We implemented a new course unit “Prevention and Counseling for Weight Management” thematizing the etiology of weight gain and weight stigma. The purpose of this study was to evaluate changes in students' weight-related attitudes after a structured educational intervention.MethodsWe used an inverted classroom design: a theoretical module for self-study followed by a practical module in presence. This evaluation study investigated the weight bias and causal attribution of 213 medical students (73.7% female) in the 6th semester. Students completed a questionnaire before and after the course, including the Fat Phobia Scale (FPS) and ratings of causal attribution. Questionnaires were generated with EvaSys©. We used t-tests, ANOVAs and Pearson correlations for analysis.ResultsAbout 96% of the students showed negative attitudes. We found an averaged weight bias in students (FPS = 3.63) and a small decrease in weight bias after the course (FPS = 3.44). The students categorized internal factors as the most important cause of weight gain. After the course, internal factors decreased while external factors increased in relevance. As not intended, biological factors of weight attribution decreased in relevance.ConclusionsThe majority of our students showed weight bias. Medical education like our course can help to reduce negative weight-related attitudes. Curricula and clinical trainings should address weight bias to raise awareness and improve health care for patients with higher weight.